High Sensitive Night-time Light Imaging Camera Design and In-orbit Test of Luojia1-01 Satellite - Su, Zhiqiang; Zhong, Xing; Zhang, Guo; Li, Yanjie; He, Xiaojun; Wang, Qiang; Wei, Zongxi; He, Chunling; Li, Deren (Sensors (Basel, Switzerland), 2019)
Luojia1-01 satellite is the first scientific experimental satellite applied for night-time light remote sensing data acquisition, and the payload is an optical camera with high sensitivity, high radiation measurement accuracy and stable elements of interior orientation. At the same time, a special shaped hood is designed, which significantly improved the ability of the camera to suppress stray light. Camera electronics adopts the integrated design of focal plane and imaging processing, which greatly reduces the volume and weight of the system. In this paper, the design of the optical camera is summarized, and the results of in-orbit imaging performance tests are analyzed. The results show that the dynamic modulation transfer function (MTF) of the camera is better than 0.17, and the SNR is better than 35 dB under the condition of 10 lx illuminance and 0.3 reflectivity and all indicators meet the design requirements. The data obtained have been widely applied in many fields such as the process of urbanization, light pollution analysis, marine fisheries detection and military.